Sustained CREB phosphorylation by lipid-peptide liquid crystalline nanoassemblies - Wu, Yu; Angelov, Borislav; Deng, Yuru; Fujino, Takehiko; Hossain, Md Shamim; Drechsler, Markus; Angelova, Angelina (Communications chemistry, 2023)
Cyclic-AMP-response element-binding protein (CREB) is a leucine zipper class transcription factor that is activated through phosphorylation. Ample CREB phosphorylation is required for neurotrophin expression, which is of key importance for preventing and regenerating neurological disorders, including the sequelae of long COVID syndrome. Here we created lipid-peptide nanoassemblies with different liquid crystalline structural organizations (cubosomes, hexosomes, and vesicles) as innovative nanomedicine delivery systems of bioactive PUFA-plasmalogens (vinyl ether phospholipids with polyunsaturated fatty acid chains) and a neurotrophic pituitary adenylate cyclase-activating polypeptide (PACAP). Considering that plasmalogen deficiency is a potentially causative factor for neurodegeneration, we examined the impact of nanoassemblies type and incubation time in an in vitro Parkinson's disease (PD) model as critical parameters for the induction of CREB phosphorylation. The determined kinetic changes in CREB, AKT, and ERK-protein phosphorylation reveal that non-lamellar PUFA-plasmalogen-loaded liquid crystalline lipid nanoparticles significantly prolong CREB activation in the neurodegeneration model, an effect unattainable with free drugs, and this effect can be further enhanced by the cell-penetrating peptide PACAP. Understanding the sustained CREB activation response to neurotrophic nanoassemblies might lead to more efficient use of nanomedicines in neuroregeneration.